Public health emergency accelerated research response—the Clinical and Translational Science Institute of Southeast Wisconsin COVID-19 research initiative - Anello, Michael P.; Ward, Doriel D.; Garrison, Orsolya M.; Gode, Amit; Ioachimescu, Octavian C.; Friedland, David R.; Shaker, Reza (Frontiers in Public Health, 2025)
IntroductionIn March 2020, the National Center for Advancing Translational Sciences—Clinical and Translational Science Awards (CTSA) Program issued an urgent “Call to Action,” requesting CTSA hubs to accelerate clinical and translational research (C&TR) in response to the COVID-19 public health emergency. The Clinical and Translational Science Institute of Southeast Wisconsin (CTSI) quickly responded by launching a regional research initiative among its eight academic and healthcare partner institutions to nucleate teams around COVID-19 C&TR.MethodsA comprehensive search of COVID-19 funding opportunities, combined with suggestions from CTSI leadership and C&TR investigators, produced a list of 31 distinct C&TR questions that were used to nucleate investigators into teams. A survey was shared with the faculty of all eight partner institutions to solicit interest in joining the teams. Multidisciplinary team formation was based on a novel CTSI model, called the “Team Science-Guided Integrated Clinical and Research Ensemble (Ensemble).” In this model, teams are formed around an unmet patient medical need, based on the intentional recruitment of members from three domains: (1) the clinical and translational research enterprise, (2) the health care systems, and (3) the community of stakeholders. The teams were provided no funding, but received substantial CTSI research and administrative support.ResultsForty-one teams were formed, and 243 investigators participated during the first year of the initiative. Team efforts resulted in the submission of 21 grant proposals, totaling 32,528,297. Three grant proposals were funded, totaling 609,888. The research initiative generated eight publications and had a significant impact on patient health, involving a combined total of 456 research participants. The initiative led to several systemic improvements, by (1) exposing investigators to team science-guided C&TR (Ensembles), (2) increasing inter-institutional and inter-departmental collaborations, (3) creating new partnerships with community organizations, and (4) providing qualitative data on lessons learned.ConclusionThe COVID-19 regional research initiative provided a compelling model of how basic science, clinical/translational, and community researchers can be mobilized for accelerated C&TR to address a public health threat. The initiative demonstrated that the fundamentals of the novel CTSI Ensemble team concept can be leveraged to expedite the formation of highly efficient teams.